A Contribution to a Politico-Liberal Model of Judgment (Diametros, 2019)
The paper intends to initiate a discussion on the politico-liberal concept of judgment. It is argued that whilst political liberalism (PL) – presented as an account of political objectivity – already appeals to judgment, this conception is an unsatisfactory one. This critical assessment is supported by the juxtaposition of PL with an Arendtian understanding of political objectivity which offers a more robust account of judgment. In the conclusion, the possibility of applying the Arendtian solution to PL is outlined.